Demystifying the impact of CEO transformational leadership on firm performance: Interactive roles of exploratory innovation and environmental uncertainty - Chen, J.; Sharma, Piyush; Zhan, W.; Liu, L. (Elsevier, 2019)
This paper aims to reconcile the inconsistent findings about the effects of CEO transformational leadership (CTL) on firm performance by using upper echelon theory to hypothesize and empirically demonstrate that CTL triggers exploratory innovation in a firm, which in turn has an inverted U-shaped effect on firm performance. In other words, CTL may only lead to better firm performance at moderate levels of exploratory innovation through optimal utilization of a firm's scarce resources and may actually hurt firm performance at higher levels of exploratory innovation because of suboptimal resource utilization. We also show that CTL's most detrimental effect on firm performance occurs when the contingencies of high technology uncertainty and low demand uncertainty are combined. Data from multiple sources within 288 Chinese firms support most of our hypotheses and provide insights into the complex mechanism by which CTL affects firm performance, especially in an increasingly uncertain global economic environment.